THE RELATIONSHIP OF PARTNER SUPPORT WITH VARIOUS ACTIVITIES OF THE ELDERLY HYPERTENSION - Farah Dwita Angelina; Joni Haryanto; Elida Ulfiana (Journal of Vocational Nursing)
Hypertension is a health problem that many elderly suffer from. Blood pressure in the elderly with hypertension can be controlled in various ways, namely doing physical activity regularly, performing activities related to cognitive function, and controlling stress levels so as not to affect contractions or pulsations of the heart and nervous system that can cause blood pressure to increase. The purpose of this study was to determine the relationship of partner support with physical, mental, and social activities of the elderly with hypertension.